Mitochondrial CaMKII causes adverse metabolic reprogramming and dilated cardiomyopathy - Elizabeth D. Luczak (Nature Portfolio, 2020)
Little is known about how cardiac metabolism remodels following cardiac injury. Here, the authors show that mitochondrial CaMKII plays an important role in remodeling cardiac metabolism after injury and that replacement of mitochondrial creatine kinase improves energetics and protects against adverse remodeling.